Bleeding and ischaemic outcomes in patients treated with dual or triple antithrombotic therapy: systematic review and meta-analysis. Issue 4 (14th June 2019) - Haller, Paul M; Sulzgruber, Patrick; Kaufmann, Christoph; Geelhoed, Bastiaan; Tamargo, Juan; Wassmann, Sven; Schnabel, Renate B; Westermann, Dirk; Huber, Kurt; Niessner, Alexander; Gremmel, Thomas
Abstract: Aims: The combination of oral anticoagulation with a P2Y12 inhibitor and aspirin in patients with atrial fibrillation (AF) undergoing percutaneous coronary intervention (PCI) is associated with a high bleeding risk. Dual antithrombotic therapy (DAT) with omission of aspirin is a promising option to reduce bleedings, but carries a yet unknown risk of ischaemic events. We therefore sought to systematically review and analyse randomized controlled trials investigating DAT vs. triple antithrombotic therapy (TAT) in patients with AF following PCI and/or acute coronary syndrome (ACS). Methods and results: We included four trials with overall 9317 patients (5039 DAT, 4278 TAT) in our analysis. Dual antithrombotic therapy was associated with a significant reduction in thrombolysis in myocardial infarction major bleeding [hazard ratio (HR) 0.52, 95% confidence interval (CI) 0.42–0.65; P = 0.0001], while the composite trial-defined ischaemic endpoint did not differ significantly between DAT and TAT (HR 0.98, 95% CI 0.79–1.22; P = 0.88). There was also no difference regarding the occurrence of myocardial infarction (MI; HR 1.16, 95% CI 0.92–1.46; P = 0.21) or stent thrombosis (HR 1.25, 95% CI 0.69–2.26; P = 0.46). Absolute numbers for MI were 131/4278 (3.1%) with TAT and 182/5039 (3.6%) with DAT, and for stent thrombosis 32/4278 (0.75%) and 52/5039 (1%), respectively. A post hoc power calculation based on the size and event rate of this meta-analysis revealed 80% power to detect a 37% and 100% increase in MI and stent thrombosis, respectively. Conclusion: Dual antithrombotic therapy significantly reduces bleedings compared with TAT and seems to have a similar effect in preventing ischaemic endpoints in AF patients post-PCI or ACS. Future investigations are needed to determine its applicability specifically in patients at high risk of ischaemic outcomes.